Evaluate the exprssion for -5a2;a=-2, and explain how its done

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Given the expression:

`-5a^2` 

We need to find the value of the expression when `a= -2`

Then, we will plug in `a= -2`  into the expression.

`==gt -5a^2 = -5(-2)^2` 

Now we will simplify and find the value.

`==gt -5a^2 = -5(4) = -20`

Then, the value of the expression...

See
This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Get 48 Hours Free Access

Given the expression:

`-5a^2` 

We need to find the value of the expression when `a= -2`

Then, we will plug in `a= -2`  into the expression.

`==gt -5a^2 = -5(-2)^2` 

Now we will simplify and find the value.

`==gt -5a^2 = -5(4) = -20`

Then, the value of the expression -5a`^2`  when a= -2 is -20.

Approved by eNotes Editorial Team